The boat - Keaton, Buster, 1895-1966; Cline, Edward, 1892-1961; Seely, Sybil, 1900-1984; First National Pictures, Inc.; Cinetel Films ([United States] : First National, 1921)
"Buster and his family are reduced to a primeval struggle to survive aboard a nightmarish vessel, the infamous Damfino.
Silent short.
"A First National attraction."
Buster Keaton, Sybil Sealey.
Silent, with English intertitles and musical accompaniment; Spanish closed-captioned.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015).
Keywords: Boatbuilding -- Drama; Boats and boating -- Drama; Ships -- Drama; Slapstick comedy films; Short films; Silent films; Feature films; Internet videos; Streaming video